Ampelopsin E reduces the invasiveness of the triple negative breast cancer cell line, MDA-MB-231 - Tieng, Francis Yew Fu; Saiful Yazan, Latifah; Md Hashim, Nur Fariesha; Khaza'ai, Huzwah; Ahmat, Norizan; Gopalsamy, Banulata; Wibowo, Agustono (MDPI, 2019)
Breast cancer is the most common and the second leading cause of cancer-related deaths in women. It has two distinctive hallmarks: rapid abnormal growth and the ability to invade and metastasize. During metastasis, cancer cells are thought to form actin-rich protrusions, called invadopodia, which degrade the extracellular matrix. Current breast cancer treatments, particularly chemotherapy, comes with adverse effects like immunosuppression, resistance development and secondary tumour formation. Hence, naturally-occurring molecules claimed to be less toxic are being studied as new drug candidates. Ampelopsin E, a natural oligostilbene extracted from Dryobalanops species, has exhibited various pharmacological properties, including anticancer and anti-inflammatory activities. However, there is yet no scientific evidence of the effects of ampelopsin E towards metastasis. Scratch assay, transwell migration and invasion assays, invadopodia and gelatin degradation assays, and ELISA were used to determine the effects of ampelopsin E towards the invasiveness of MDA-MB-231 cells. Strikingly in this study, ampelopsin E was able to halt migration, transmigration and invasion in MDA-MB-231 cells by reducing formation of invadopodia and its degradation capability through significant reduction (p < 0.05) in expression levels of PDGF, MMP2, MMP9 and MMP14. In conclusion, ampelopsin E reduced the invasiveness of MDA-MB-231 cells and was proven to be a potential alternative in treating TNBC.